Endolymphatic Drug Delivery Improves Outcomes in Persistent Postoperative Peritonitis - Usarov A.M.; Ashurmetov A.M.; Fayziyev Y.N. (Universitas Muhammadiyah Sidoarjo, 2026)
Postoperative peritonitis remains a critical challenge in contemporary surgery, with persistent complications despite conventional antibiotic therapy leading to increased mortality and prolonged recovery periods. This study investigates the therapeutic efficacy of direct endolymphatic drug therapy (TTBET) in managing persistent postoperative peritonitis following acute appendicitis. The research examined 66 patients with appendicular peritonitis treated in Tashkent surgical clinics, divided into a main group receiving endolymphatic therapy via catheterized peripheral lymphatic vessels (n=36) and a control group receiving conventional treatment (n=30). Immunological parameters including T-lymphocytes, B-lymphocytes, immunoglobulins (IgG, IgA, IgM), and neutrophil phagocytic activity were measured at baseline and day 14 post-treatment using standardized biochemical and immunological assays. Results demonstrated statistically significant improvements in the endolymphatic therapy group, with T-lymphocyte counts increasing 1.41-fold compared to controls (p=0.0022), IgG levels rising 1.7-fold versus 1.49-fold in controls, and neutrophil phagocytic activity improving 1.68-fold versus negligible change in the control group. This study provides novel evidence that endolymphatic administration achieves superior drug concentration at inflammatory sites while simultaneously modulating immune responses through direct lymphatic system engagement. The findings suggest endolymphatic therapy represents a pathogenetically sound approach for managing persistent peritonitis, offering reduced antibiotic doses, enhanced immunological recovery, and improved clinical outcomes, warranting broader clinical implementation in surgical infection management protocols.Keywords : Endolymphatic Drug Administration, Postoperative Peritonitis Management, Lymphatic System Therapeutics, Immunomodulation Surgical Infections, Regional Antibiotic Delivery, Purulent-Septic ComplicationsHighlight : Endolymphatic therapy significantly increases T-lymphocytes, immunoglobulins IgG/IgM, and neutrophil phagocytic activity Main group shows 1.41-fold T-lymphocyte increase versus minimal improvement in control group Treatment normalizes microcirculation and reduces postoperative complications in appendicular peritonitis patients.